Poetry and Revolution: study on the prominent political and social affairs in the poetry of the constitutional revolution’s (1905-1925) - Saeed, Raouf M. (Humanities Journal of University of Zakho, 2018)
The Constitutional Revolution in Persia has resulted in a number of great changes in poetry in particular and in literature in general. It should be born in mind that the revolution was by itself the fruit of some new thoughts and beliefs that appeared and got mirrored in poetry then. Poetry had a vital role in sharpening people’s awareness of their legal human rights. Generally speaking, we can detect all sorts of the changes embodied in poetry of that age. Poetry of the constitution era was mainly of political flavor linked to the revolution. Poets then held concepts like patriotism, freedom, the dispute between local dictatorship and foreign interference, and feminism. This study is an attempt to investigate the prominent political and social affairs in the poetry of the constitutional revolution’s era in Persia.